Teachers’ proof or teacher proof? The influence of performativity on teachers’ practice in South African classrooms - Badal, Bernice (Journal for Language Teaching, 2024)
Using the meta-theoretical tenets of social constructivism and the conceptual framework of Stephen Ball (2003), this qualitative study investigated teachers’ perceptions and practices in highly regulated reform policy contexts. Data capture involved semi-structured inter¬views and observations conducted over the period of a school year. Findings revealed that accountability and performativity measures that are aligned with the current reform have increased the complexity of teachers’ practices, intensified labour and heightened their need for compliance. The data revealed a dissonance between the perceptions of policy bureaucrats and teachers in relation to the efficacy of statistical goals within the paradigm of performativity However, the main factor that motivated teachers’ compliance and conformity hinged on the creation of a favourable impression and an appeasement of external agents. The central position of this article, how¬ever, holds that suppressing teachers’ professional judgement leads to the neglect of crucial learning goals such as learner motivation and critical thinking which are crucial aims of schooling. English teachers are best placed to support this type of learning, but it is doubtful whether silenced teachers can raise critical learners.